Straight from foster care to the youth detention center? The (mis)paths of child protection and juvenile justice policies in the construction of violent masculinities - Mascarenhas, Marta (Frontiers in Sociology, 2025)
The present article aims to understand how public policies for the protection of endangered children/youngsters and juvenile justice work together or, on the contrary, in a disjointed way, and its impacts on the reproduction of gender stereotypes, namely in the construction of rigid masculinities of youngsters in detention and the adoption of violence as an adaptive strategy. Youth Detention Centers (YDC) were chosen as a backdrop since young people at risk are a particular fringe of society who, similar to other vulnerable groups (e.g., migrants, refugees, etc.), face more significant risks of GBV, since they are displaced from their families and communities when they are admitted at Portuguese YDCs and their paths have invariably been marked by having witnessed or been exposed to violence, and often, as we shall see, to protective institutionalization at an early stage in their journey. To this end, the role of YDC's will be traced within the framework of public policies on juvenile justice in Portugal, exploring the evolution of public policies aimed at both the risk and the social danger of children and young people, namely the effects of the separation that has taken place in Portugal of these two domains in the face of the effects of the promiscuity between the domain of danger and that of social risk. Results of the X-MEN Project, namely the youngsters' narratives on their life trajectories until entering the YDC, will be used to illustrate the relationship between gender socialization (particularly of boys), the interpenetration between protective institutionalization and its predictor of a pre-delinquent path and, finally, how gender can be the basis for differentiated treatment by the systems that work with young people in danger (Child Protection System) and at risk (Juvenile Justice System).